"Šolski tolar" kot razvojna politika na znanju temelječe družbe - Šela, Ana (Studia Historica Slovenica, 2025)
This article examines the genesis, content, and systemic impact of the Act on Securing Funds for Certain Urgent Development Programs in Education (19941999), popularly referred to as the "School Money" (šolski tolar). Adopted in the early years of Slovenian statehood, the Act represented a pivotal moment in the development of education policy in a post-socialist context. It provided a dedicated, multi-annual fiscal mechanism to support strategic priorities in education – school infrastructure, computer literacy, foreign language learning, textbook accessibility, and school nutrition – thus addressing both developmental and social dimensions of the education system. The article situates the Act within the broader reform trajectory of the 1990s, which can be described as a three-phase process: (1) organizational restructuring and fiscal stabilization in the early 1990s, (2) curriculum reform in the mid1990s, and (3) implementation and evaluation by the end of the decade. Within this sequence, the "School Money" is conceptualized as a bridging instrument that connected the strategic visions of the White Paper on Education (1995) with the practical capabilities of the system, filling a typical "implementation gap" common in transitional societies. The Act ensured predictable funding, thereby enabling sustained modernization and facilitating subsequent curricular reforms. Parliamentary debates and archival sources reveal the exceptional consensus that surrounded the Act' s adoption. Promoted across party lines as a "law of all deputies", the initiative was marked by the personal dedication of MP Rudi Moge and Minister of Education Slavko Gaber, who emphasized that long-term national security was equally dependent on knowledge as on military defence. Symbolically, the financing was partly secured by reallocating resources from defence to education, highlighting a deliberate shift in priorities in favour of human capital. The Act' s outcomes were significant. By 1998, Slovenian schools had achieved a rapid increase in computer equipment, with one computer per 28 pupils in primary schools and one per 9.5 students in secondary schools. Foreign language instruction was expanded, textbook rental systems in libraries improved accessibility, and school meals were recognized as an essential element of educational equity and public health. However, empirical evaluations also revealed limits: while material infrastructure was strengthened, the pedagogical integration of new technologies and sustained professional development remained uneven and dependent on local leadership and teacher competencies. From a comparative perspective, the "School Money" stands out among post-socialist reforms for its ex-ante fiscal stabilization, which contrasted with the ad hoc or donor-dependent approaches in many neighbouring countries. Its systemic design allowed Slovenia to align with European trends in informatization, multilingualism, and social inclusiveness in education, thus reinforcing the foundations of a knowledge-based society. The article concludes by reflecting on the contemporary relevance of the Act. Just as computer literacy was recognized as a strategic imperative in the 1990s, today artificial intelligence and digital competencies represent comparable challenges that demand forward-looking, consensus-based investment policies. The legacy of the "School Money" underscores the enduring importance of political will, cross-party cooperation, and fiscal commitment in translating strategic visions into sustainable reforms.
Keywords: izobraževalna politika; šolski tolar; tranzicija; vzgoja in izobraževanje; Zakon o zagotavljanju sredstev za nekatere nujne razvojne programe v vzgoji in izobraževanju